Unraveling the effect of body structure score on phenotypic plasticity for body weight at different ages in Guzerat cattle - Mota, Lucio F.M. [UNESP]; Costa, Leonardo S.; Garzón, Natalia A.M. [UNESP]; Passafaro, Tiago L.; Silva, Diogo O. [UNESP]; Abreu, Luiza R.A.; Verardo, Lucas L.; Bonafé, Cristina M.; Ventura, Henrique T. (Elsevier, 2019)
The Body structure (BS) is a trait to be considered in the genetic evaluation of beef cattle because it is associated with economically important traits, maintenance requirement, and physiological maturity. Therefore, the objective of this study was to determine the effect of genotype-environment (GxE) interaction considering contemporary group solutions for BW and BS as an environmental gradient (EG) to assess the changes in the body weight (BW). For this BW was measured at 120, 205, 365, 450 and 550 days of age in Guzerat cattle. Phenotypic data from 21,973 Guzerat animals were used to explore the GxE effect among BW, obtained from 150 farms distributed in five Brazilian States provided by the Brazilian Association of Zebu Breeders. A reaction norm model in two-steps was used to estimate the animals’ response to environmental changes. As evidence of GxE, heterogeneity of genetic variance across environments was observed for BW at different ages. Changes in heritability estimates ranged from 0.29 to 0.44 for BW and provided differences in the selection response across different EG levels. The genetic correlations between extreme EG levels indicated a strong effect of GxE interactions. Breeding value for BW at 120 and 205 days of age showed less plasticity than BW at 365, 450, and 550 days of age due to changes in EG. Nevertheless, these results indicate that the BS is an important factor to be considered in genetic evaluations for BW according to the growth phase.
Keywords: Animal sensitivity; Body structure; Genotype-environment interaction; Performance trait